Η «Εικονοκλαστική» ΝΟΤΙΤΙΑ 3 και το λατινικό της πρότυπο - ΚΟΥΝΤΟΥΡΑ-ΓΑΛΑΚΗ Ελεωνόρα (Byzantina Symmeikta, 1996)
Eleonora Kountoura-Galaki The «iconoclastic» Notitia 3 and its latin origins A well known passage in Theophanes’ Chronographia mentions the annexation of Illyricum to the jurisdiction of the Patriarchate of Constantinople by the iconoclast emperor Leo III. New metropolitan sees and bishoprics were then incorporated into the byzantine ecclesiastical hierarchy and this new status can be traced in the «iconoclastic» Notitia 3. The names of the new metropoleis and bishoprics from the Illyricum area are unusual, but the origins of these strange names is unknown. By examining the scribal hand in latin manuscript sources and the sigillographie trends of the seventh century, especially in the case of the letters A, H and R, I have attempted to show that behind this Notitia lies a text originally written in Latin.